Pengaruh Kualitas Pelayanan Dan Produk Terhadap Kepuasan Nasabah Di Bank Syariah Indonesia KCP Jayapura Abepura Provinsi Papua - Permana, Dwi Arya (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze the effect of product quality and service quality on customer satisfaction. This research was conducted at Bank Syariah Indonesia Sub-Branch Office Jayapura, Abepura, Papua Province. The sample in this study was customers of Bank Syariah Indonesia Sub-Branch Office Jayapura Abepura Papua Province, totaling 80 respondents. This research is quantitative and data analysis technique using SPSS. The results of this study show that the variable of service quality has a significant effect and the variable of product quality has a significant effect on customer satisfaction. Keywords: Service Quality, Quality Product, Customer Satisfactions, SPSS.